Elements of Entrepreneur Competencies and Intention to be Entrepreneurs - Christine Winstinindah Sandroto; Yussi Ramawati; Syarief Darmoyo (International Journal of Applied Business and International Management, 2024)
This study aims to determine the effect of the elements of entrepreneurial competencies on entrepreneurial intention in two big cities in Indonesia, namely Jakarta and Balikpapan. The population in this study are business people, both entrepreneurs and those who work in creative industries in Jakarta and Balikpapan. The number of respondents in Jakarta and Balikpapan was 305 and 162. The sampling technique used was convenience sampling.  This research revealed that certain competencies, such as achievement, personal maturity, and orientation to others, had a partially positive and significant impact on entrepreneurial intention among the respondents in Jakarta. Conversely, competencies like thinking problem solving, influence, and direct and controlling showed no effect. On the other hand, in Balikpapan, respondents' entrepreneurial intention was significantly influenced by achievement competence and thinking and problem-solving, while competencies like personal maturity, influence, direction and control, and orientation to others did not play a role in shaping the intention to become an entrepreneur. The research underscores the potential for refining entrepreneurial competency frameworks based on the specific competencies that influence entrepreneurial intention.